(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
An exploration of Madonna as a conduit to discuss the concept of relevance. The presentation explores the relevance of psychotherapy today, the dangers of ideological polarisation, the artistry of therapy and the importance of nuance. It explores the categories of gender, race and power and the importance of psychotherapy to create spaces from where they can be engaged with consciously, courageously and constructively.